A review of divorce information management system - Aziman, Abdullah; Asar, Abdul Karim; Solehah, Shamsuddin; Mohammad Affendy, Omardin (IOP Publishing, 2020)
The social issue associate with divorce is not on the divorce process itself but rather than the impact to the individuals who experience divorce. Since divorce already become a stigma in society, most people perceived more on negative view instead of seeing it as a process to solve issues in marriage. With the high penetration of Internet technology globally especially the use of social network, it becomes a factor how people can cheat in marriage that lead to divorce. However, studies on the use of Internet or information technology in managing divorce is still lack. This paper aims to analyse the existing literature in Scopus database on divorce information management system and identify targeted stakeholders of the system. Our findings confirmed that there is lack of study on divorce information management system.